Characteristic of the power decay length of small ELMs measured by infrared camera on EAST - G.T. Chen; Q.Q. Yang; J.H. Yang; X. Lin; H. Yang; Z.D. Yang; R.R. Liang; T.H. Wang; B.H. Zhang; L. Wang; Y.W. Sun; G.S. Xu; et al. (Nuclear Fusion)
Small edge-localized-mode (ELM) regimes are being studied as promising solution to reduce the heat flux to the first-wall within tolerable levels in future machines. This study represents the first utilization of a high-resolution infrared camera system on the Experimental Advanced Superconducting Tokamak to investigate the heat flux characteristics of small ELMs. Both typical discharge results and statistical analyses indicate that the power decay length ( ${λ _q}$ ) of small ELMs is broader than that of inter-large ELMs but narrower than that of intra-large ELMs, consistent with previous simulations using the BOUT++ code. Further analysis indicates that low hybrid wave heating has a more significant impact on the ${λ _q}$ of small ELMs compared to other heating schemes. Among all the parameters, the line averaged density ( ${n_{{\text{el}}}}$ ) has the most notable effect on the heat flux width of small ELMs, as evidenced by both the correlation analysis and the result from typical shots. Furthermore, the investigation on the heat load deposition in far-scrape-off-layer (SOL) region during small ELMs shows that small ELMs under relatively low collisionality conditions, carrying less than 1% of the plasma stored energy, are found to deposit 0.2–0.45 of the ELM power to the far SOL region.